2016
DOI: 10.1007/s00439-016-1654-x
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific transcription factor binding to common and rare variants associated with disease and gene expression

Abstract: Genome-wide association studies (GWAS) have identified a large number of disease-associated SNPs, but in few cases the functional variant and the gene it controls have been identified. To systematically identify candidate regulatory variants, we sequenced ENCODE cell lines and used public ChIP-seq data to look for transcription factors binding preferentially to one allele. We found 9962 candidate regulatory SNPs, of which 16 % were rare and showed evidence of larger functional effect than common ones. Function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 34 publications
0
56
1
1
Order By: Relevance
“…Interestingly, whereas these show minimal evidence of acting as regulatory polymorphisms according to RegulomeDB (score 5 and 4, respectively), rs9603612 seems to influence the COG6 expression in monocytes, thus representing a better candidate to be the causal variant involved in the genetic predisposition to these three autoimmune conditions. Indeed, a very recent study focused on identifying functional variants for disease-associated loci , has confirmed this regulatory role of the rs9603612 polymorphism 32. Specifically, the minor allele (G) was found to increase the COG6 expression compared with the major allele, thus supporting that rs9603612 influences the development of SLE, RA and psoriasis by regulating the COG6 levels.…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, whereas these show minimal evidence of acting as regulatory polymorphisms according to RegulomeDB (score 5 and 4, respectively), rs9603612 seems to influence the COG6 expression in monocytes, thus representing a better candidate to be the causal variant involved in the genetic predisposition to these three autoimmune conditions. Indeed, a very recent study focused on identifying functional variants for disease-associated loci , has confirmed this regulatory role of the rs9603612 polymorphism 32. Specifically, the minor allele (G) was found to increase the COG6 expression compared with the major allele, thus supporting that rs9603612 influences the development of SLE, RA and psoriasis by regulating the COG6 levels.…”
Section: Discussionmentioning
confidence: 74%
“…Further annotation of this DHS revealed that it overlapped with an erythroid enhancer chromatin signature as defined in primary human erythroid precursors (17) and with several GATA1-binding motifs, and harbored multiple erythroblast-specific eQTLs in strong LD that were associated with ATP2B4 expression and rbc phenotypes ( Figure 2D and Figure 3A). Supporting the regulatory potential of this DHS in erythroid cells, a recent analysis of ENCODE data found that it showed allele-specific transcription factor binding only in K562 cells (20).…”
Section: Eqtl Mapping In Erythroblasts Identifies Cell-specific Assocmentioning
confidence: 82%
“…For instance, the classification model may be under-fitted because the number of ASB events available for training was not sufficient. In the review stage of this manuscript, two studies compiled new ASB data sets in other cell lines to investigate GWAS loci or the variant impact on gene expression (17,57). In the future, we anticipate a rapidly growing body of ASB data will be critical in training more reliable models.…”
Section: Discussionmentioning
confidence: 99%